2015
DOI: 10.1177/0148607115597670
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ω‐3 Polyunsaturated Fatty Acids on the Homeostasis of CD4+ T Cells and Lung Injury in Mice With Polymicrobial Sepsis

Abstract: A fish oil diet with an ω-6/ω-3 PUFA ratio of 2:1 may elicit more balanced Th polarization, alleviate inflammatory responses, and attenuate lung injury in CLP-induced sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Neopterin is a marker of monocyte and macrophage activation by T-helper 1 (TH1) cells in response to infection. An improved nutrient supply can reduce Th1 cell cytokine production to achieve a more balanced inflammatory response [73][74][75]. Compared to non-WASH, we observed a small decrease in kynurenine at 12 months and an increase in IGF-1 at 18 months in the WASH group after multiple testing correction, but no impact on any other biomarkers.…”
Section: Geometric Means Pointwise 95% Confidence Intervals and The mentioning
confidence: 63%
“…Neopterin is a marker of monocyte and macrophage activation by T-helper 1 (TH1) cells in response to infection. An improved nutrient supply can reduce Th1 cell cytokine production to achieve a more balanced inflammatory response [73][74][75]. Compared to non-WASH, we observed a small decrease in kynurenine at 12 months and an increase in IGF-1 at 18 months in the WASH group after multiple testing correction, but no impact on any other biomarkers.…”
Section: Geometric Means Pointwise 95% Confidence Intervals and The mentioning
confidence: 63%
“…In this study, mice subjected to CLP-induced sepsis followed by fluid resuscitation and antibiotic treatment all survived the experiment, as witnessed at 72 h post-CLP. In a previous report, the same model without antibiotic treatment resulted in 75%–88% survival by 48 h after CLP [ 23 ]. It can be expected that the use of antibiotics improves survival.…”
Section: Discussionmentioning
confidence: 94%
“…A previous study found that naïve T cell activation and their responses were adversely affected during sepsis (6) . A significant decline of CD4 + T cell numbers in spleen and peripheral blood at 72 h post CLP were reported (26,27) . Consistent with the studies mentioned earlier, we also found that the percentages of circulating and splenic T lymphocytes and CD4 + T cells decreased.…”
Section: Discussionmentioning
confidence: 97%